[Uf6]2−: A Molecular Hexafluorido Actinide(Iv) Complex with Compensating Spin and Orbital Magnetic Moments - Aravena-Ponce, D; Aravena-Ponce, D (Wiley-VCH Verlag, 2019)
The first structurally characterized hexafluorido complex of a tetravalent actinide ion, the [UF6]2− anion, is reported in the (NEt4)2[UF6]⋅2 H2O salt (1). The weak magnetic response of 1 results from both UIV spin and orbital contributions, as established by combining X-ray magnetic circular dichroism (XMCD) spectroscopy and bulk magnetization measurements. The spin and orbital moments are virtually identical in magnitude, but opposite in sign, resulting in an almost perfect cancellation, which is corroborated by ab initio calculations. This work constitutes the first experimental demonstration of a seemingly non-magnetic molecular actinide complex carrying sizable spin and orbital magnetic moments. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim